2018
DOI: 10.1002/admt.201800152
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Molecular Polarizability of SAMs on the Work Function Modification of Gold: Closed‐ versus Open‐Shell Donor–Acceptor SAMs

Abstract: Charge injection barriers at metal/organic interfaces can be tuned by modifying the work function of metallic electrodes using self‐assembled monolayers (SAMs) of polar molecules. An interesting example of polar molecules is offered by donor–acceptor (D–A) dyads based on ferrocene (Fc) as electron‐donor unit and either a polychlorotriphenylmethyl radical or a polychlorotriphenylmethane as electron‐acceptor units, connected by a π‐conjugated vinylene bridge. The D–A radical exhibits high chemical and thermal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 43 publications
(47 reference statements)
1
23
0
Order By: Relevance
“…5c and d). In our previous work, 22 we demonstrated that the polarizability of radical molecules in SAM S2 is higher than in SAM S1, meaning that the surface dipole in S2 is more sensible to the changes in the surrounding charge density. Consequently, the negative shift induced by the thermal motion is higher in the case of the radical SAM S2 (B285 meV) than in the non-radical SAM S1 (B145 meV).…”
Section: Effect Of the Temperaturementioning
confidence: 80%
See 4 more Smart Citations
“…5c and d). In our previous work, 22 we demonstrated that the polarizability of radical molecules in SAM S2 is higher than in SAM S1, meaning that the surface dipole in S2 is more sensible to the changes in the surrounding charge density. Consequently, the negative shift induced by the thermal motion is higher in the case of the radical SAM S2 (B285 meV) than in the non-radical SAM S1 (B145 meV).…”
Section: Effect Of the Temperaturementioning
confidence: 80%
“…The reported values of Df, as obtained by KPFM measurements using an in situ reference surface, were 50 meV and 22 meV for the non-radical S1 and radical S2 SAMs, respectively. 22 We demonstrated that the radical form has a larger polarizability than the non-radical molecules, pointing to larger depolarization effects in the former case due to its higher charge-transfer character. This implies that the permanent dipole of a given molecule (m i ) is modified to a stronger extent in S2 due the charge redistribution that takes places upon interacting with the electric field generated by the dipoles of the neighbouring molecules within the SAM, thus rationalizing the lower WF values of S2 with respect to S1.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations